2017
DOI: 10.1039/c6ra28757c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new conjugated polymers with coordinated praseodymium complexes for polymer memory devices

Abstract: A series of novel praseodymium(Pr)-coordinated polymers with fluorene, phthalimide and bipyridine moieties in the main chain were synthesized via a coordination reaction and palladium-catalyzed Suzuki coupling polycondensation. Their structures, optical features and memory performance have been well studied. A resistive switching device with the configuration of ITO/polymer/Al was constructed using a spin-coating process. The device exhibits nonvolatile write-once-read-many-times (WORM) memory behavior. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recently, by changing the ratio of monomers, Ling et al reported a series of novel conjugated Pr-containing polymers (PFPh(BipyPr) n ) (P43) with fluorene, phthalimide and bipyridine moieties in the main chain through the coordination reaction and palladium-catalyzed Suzuki coupling polycondensation. 162 It was discovered that the memory characteristic is strongly dependent on the loading content of Pr(III) complex. For example, the Pr-containing polymer with 2.9 mol% of Pr(III) complex showed a WORM-type memory behavior with a low threshold voltage (1.68 V) and quite low I ON /I OFF ratio of only 10.…”
Section: Cu-containing Metallopolymersmentioning
confidence: 99%
“…Recently, by changing the ratio of monomers, Ling et al reported a series of novel conjugated Pr-containing polymers (PFPh(BipyPr) n ) (P43) with fluorene, phthalimide and bipyridine moieties in the main chain through the coordination reaction and palladium-catalyzed Suzuki coupling polycondensation. 162 It was discovered that the memory characteristic is strongly dependent on the loading content of Pr(III) complex. For example, the Pr-containing polymer with 2.9 mol% of Pr(III) complex showed a WORM-type memory behavior with a low threshold voltage (1.68 V) and quite low I ON /I OFF ratio of only 10.…”
Section: Cu-containing Metallopolymersmentioning
confidence: 99%
“…Beyond pure organic molecules, metal coordination complexes with transition metal species of Pt, Ir, Eu and Pr that contain 4d electrons can also act as electron acceptor chromophores in D–A type conjugated polymer memristive materials. For instance, Ling and co‐workers synthesized two π ‐conjugated D–A polymers, P6 and P7, with 5,5′‐disbromo‐2,2′‐bipyridine or Pr complex as the acceptor moieties, and explored their electrical memory characteristics 71 . The results show that P6 does not exhibit any electrical bistability, while P7 displays WORM memory characteristics.…”
Section: Conjugated Memristive Polymers For Data Storage Memoriesmentioning
confidence: 99%
“…Organic field-effect transistors (OFETs), which consist of conjugated polymers as a channel layer, have been extensively studied due to their potential in all-printed electronics featuring flexible and rollable shapes. [1][2][3][4][5][6][7] To date, OFETs with conjugated polymers have been attempted for various applications such as photodetectors, [8][9][10][11] tactile sensors, [12][13][14] biosensors, [15][16][17] memory devices, [18][19][20] etc. In particular, keen attention has been paid to the photodetector applications of OFETs, leading to organic phototransistors (OPTRs), as most conjugated polymers with monomeric units of short conjugation lengths exhibit strong optical absorptions in the ultraviolet [21][22][23][24][25][26] and visible light ranges.…”
Section: Introductionmentioning
confidence: 99%